Franšīzes izmantošana auto nomas uzņēmumos Latvijā - Burtniece, Ramona (Latvijas Universitāte, 2009)
Bakalaura darbs „Franšīzes izmantošana auto nomas uzņēmumos Latvijā”. Darba mērķis: izpētīt preču zīmes nozīmi starptautiskajā tirdzniecībā un franšīzē, analizējot uz franšīzes pamata darbojošos auto nomas uzņēmumu darbību Latvijā, to iespējamās priekšrocības vai zaudējumus salīdzinājumā ar vietējiem uzņēmumiem. Darba ietvaros izpētīts preču zīmes jēdziens, franšīzes būtība, likumdošana, kas to regulē, analizēta un salīdzināta 2 uz franšīzes pamata darbojošos auto nomu darbība un, veicot auto nomu klientu anketēšanu, noteikts, kādas ir šo uzņēmumu priekšrocības, salīdzinājumā ar vietējiem uzņēmumiem. Darbā veikta SVID analīze un izstrādāti priekšlikumi auto nomu darbības uzlabošanai. Atslēgvārdi: starptautiskā tirdzniecība, preču zīme, franšīze, auto noma.

ANOTATION Bachelor thesis „Application of franchise in car rent companies in Latvia”. The aim of the thesis: to study the meaning of the trademark in the international trade and the franchising by the means of the analysis of the car rent companies operating in Latvia on the basis of franchise, the possible advantages or losses compared to local companies. The concept of trademark, the essence of franchise and the governing legislation has been analysed in the thesis, and the comparison of two car rent companies operating on the basis of franchise has been performed. The advantages of these companies compared to local companies have been defined by carrying out the survey among the clients of the car rent companies. The SWOT analysis has been included and the proposals for the improvement of the car rent company operation have been developed in the bachelor thesis. Keywords: international trade, trademark, franchise, car rent.
Application of franchise in car rent companies in Latvia
Keywords: Vadībzinātne